The Impact of Air Pollution, Including Asian Sand Dust, on Respiratory Symptoms and Health-related Quality of Life in Outpatients With Chronic Respiratory Disease in Korea: A Panel Study - Motoyuki Nakao; Yoko Ishihara; Cheol-Hong Kim; In-Gyu Hyun (Korean Society for Preventive Medicine, 2018)
Objectives Air pollution is a growing concern in Korea because of transboundary air pollution from mainland China. A panel study was conducted to clarify the effects of air pollution on respiratory symptoms and health-related quality of life (HR-QoL) in outpatients with and without chronic obstructive pulmonary disease (COPD) in Korea. Methods Patients filled out a questionnaire including self-reported HR-QoL in February and were followed up in May and July. The study was conducted from 2013 to 2015, with different participants each year. Air quality parameters were applied in a generalized estimating equation as independent variables to predict factors affecting HR-QoL. Results Lower physical fitness scores were associated with Asian sand dust events. Daily activity scores were worse when there were high concentrations of particulate matter (PM) less than 10 μm in diameter (PM10). Lower social functioning scores were associated with high PM less than 2.5 μm in diameter and nitrogen dioxide (NO2) concentrations. High NO2 concentrations also showed a significant association with mental health scores. Weather-related cough was prevalent when PM10, NO2, or ozone (O3) concentrations were high, regardless of COPD severity. High PM10 concentrations were associated with worsened wheezing, particularly in COPD patients. Conclusions The results suggest that PM, NO2, and O3 cause respiratory symptoms leading to HR-QoL deterioration. While some adverse effects of air pollution appeared to occur regardless of COPD, others occurred more often and more intensely in COPD patients. The public sector, therefore, needs to consider tailoring air pollution countermeasures to people with different conditions to minimize adverse health effects.